Serum Phosphate and Cognitive Function in Older Men - Slinin, Yelena (Int J Geriatr Psychiatry, 2017)
OBJECTIVE: Determine whether serum phosphate is associated with concurrent cognitive impairment and subsequent cognitive decline in older men independent of demographic covariates and atherosclerotic risk factors. METHODS: In a prospective study of 5,529 men enrolled in the Osteoporotic Fractures in Men (MrOS) study, we measured baseline serum phosphate, baseline cognitive function, and change in cognitive function between baseline and follow-up exams an average of 4.6 years later using the Modified Mini-Mental State (3MS) examination and Trails B. RESULTS: There was no association between serum phosphate and odds of cognitive impairment as assessed by baseline 3MS score or risk of cognitive decline as assessed by longitudinal change in 3MS score. Higher baseline serum phosphate was associated with higher odds of poor executive function as assessed by Trails B with fully adjusted odds ratios (OR) 1.12 (95% confidence interval [CI]: 0.83–1.52), 1.31 (0.97–1.77), and 1.45 (1.08–1.94) for men in the 2nd, 3rd, and 4th versus the bottom quartile (referent group) of serum phosphate (p-trend 0.007). However, higher phosphate level was not associated with risk of decline in executive function as assessed by longitudinal change in Trails B score with fully adjusted OR 0.94 (95% CI 0.69–1.28), 0.96 (0.70–1.32), 1.21 (0.89–1.66) for men in the 2nd, 3rd, and 4th versus the bottom quartile (referent group) of serum phosphate (p-trend 0.22). CONCLUSIONS: Higher serum phosphate in older men was associated with a higher likelihood of poor executive function, but not with impaired global cognitive function or decline in executive or global cognition.